2017
DOI: 10.3390/s17102373
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Wireless Sensor System with the Algorithms of Heart Rate and Agility Index for Athlete Evaluation

Abstract: Athlete evaluation systems can effectively monitor daily training and boost performance to reduce injuries. Conventional heart-rate measurement systems can be easily affected by artifact movement, especially in the case of athletes. Significant noise can be generated owing to high-intensity activities. To improve the comfort for athletes and the accuracy of monitoring, we have proposed to combine robust heart rate and agility index monitoring algorithms into a small, light, and single node. A band-pass-filter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It is the result of a multidisciplinary development that combines sensor technology, wireless transmission technology, distributed information technology, and embedded technology. Processing technology can collect, process, and transmit object information to objects that need to be sensed [1][2][3]. The WSN has a wide range of applications, from environmental monitoring, industrial processing control to military applications; you can see the WSN [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is the result of a multidisciplinary development that combines sensor technology, wireless transmission technology, distributed information technology, and embedded technology. Processing technology can collect, process, and transmit object information to objects that need to be sensed [1][2][3]. The WSN has a wide range of applications, from environmental monitoring, industrial processing control to military applications; you can see the WSN [4].…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate for athletes is an instrument to determine and monitor their daily effort for every training and how hard their body is being trained. A slower increase in heart rate while training sessions act as proof that athletes are physically fit (Aubert et al, 2003; Li and Kim, 2017). Although a slower heart rate is preferable, the small differences between the comparators have indicated that WPS is capable and comparable to the comparators.…”
Section: Discussionmentioning
confidence: 99%
“…(1) HR Extraction . HR was defined by calculating the R - R duration/interval time among QRS complexes of consecutive ECG waveforms within 1 minute intervals, where R was the first upward deflection wave after the P wave, the QRS complex was a series of waveforms following the P wave in the ECG waveforms, and the R-R interval was the elapsed time between two consecutive R waves [25, 26].…”
Section: Methodsmentioning
confidence: 99%
“…The autoalarm feature of the proposed system was based on the threshold value determination of monitored physiological parameters, such as HR, which reflects certain cases of ECG abnormalities and is considered as an indicator of a motion function [28]. In this study, HR was extracted and calculated from ECG waveforms on the basis of an algorithm proposed in [25], and the HR threshold values were determined based on works [13, 26].…”
Section: Methodsmentioning
confidence: 99%